John Moores Liverpool Exhibition 13. - Walker Art Gallery, Liverpool (Liverpool : Walker Art Gallery, 1982)
Atkins, Raymond Kenneth ; Ayling, Brian ; Ayres, Gillian ; Bellany, John ; Benjamins, Paul ; Berg, Adrian ; Booker, Alex ; Camp, Jeffery ; Carter, Tony ; Cockcroft, David ; Cockrill, Maurice ; Cook, Barrie ; Couch, Christopher John ; Crowley, Graham ; Crowley, Lucy Mary Catherine ; etc.
John Moores Liverpool Exhibition 13, Walker Art Gallery, Liverpool, November 25th 1982 to February 20th 1983
boek